Two-photon small-molecule fluorescence-based agents for sensing, imaging, and therapy within biological systems. (21st January 2021) - Wu, Luling; Liu, Jihong; Li, Ping; Tang, Bo; James, Tony D.
Abstract : In this tutorial review, we will explore recent advances for the design, construction and application of two-photon excited fluorescence (TPEF)-based small-molecule probes. Abstract : In this tutorial review, we will explore recent advances for the design, construction and application of two-photon excited fluorescence (TPEF)-based small-molecule probes. The advantages of TPEF-based probes include deep tissue penetration and minimal photo-damage. We discuss the underlying two-photon (TP) fluorophores including hemicyanine and design strategies such as Förster resonance energy transfer (FRET). Moreover, we emphasize applications for the detection or imaging of cations, anions, small neutral molecules, biomacromolecules, cellular microenvironments, subcellular localization and dual-responsive systems. Examples of photodynamic therapy (PDT) using TP irradiation are also illustrated.